Examining The Validity Of Using A Bilingual Test To Assess Form Two Students’ Achievement In Mathematics - Shanmugam, S.Kanageswari Suppiah (2010)
The aim of this study is to compare the construct equivalence of the English-only test and the bilingual test by using dimensionality and differential item functioning methods. In addition, this study also examines the differences in the mathematical achievement between the limited English proficiency students’ (LEP) and the non-LEP students in both tests for computation and word-problem testlets. By using spiral administration, all the LEP students in the six classes that had been selected sat for the tests simultaneously.